2016
DOI: 10.1148/radiol.2015142230
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Dose Dependency Analysis of Whole-Brain CT Perfusion Imaging

Abstract: The total dose of a clinical cerebral CT perfusion protocol can be lowered to 2.5 mSv, with only minor quantitative effects on perfusion values. Dose reduction beyond this point resulted in overestimation of perfusion values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…An overview of the configurations used in this work is given in Table 2. Five studies are presented of which two have been published separately (Van den Boom et al, 2014; Manniesing et al, 2016). …”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An overview of the configurations used in this work is given in Table 2. Five studies are presented of which two have been published separately (Van den Boom et al, 2014; Manniesing et al, 2016). …”
Section: Experiments and Resultsmentioning
confidence: 99%
“…There are no definite answers which method should be used, but the digital phantom provides a direct mean to investigate these properties. For example, by duplicating the dose dependency study (Manniesing et al, 2016) for different perfusion analysis methods, the difference of their responses can be quantified and their robustness to noise can be assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nine-sweep CBCTP acquisition protocol used in this study, a total radiation dose of 4.6 mSv 9 were delivered to the patient. The dose from a state-of-the-art diagnostic CTP exam is 5.0 mSv 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the high radiation dose, cerebral VP CT received little attention. Few technical studies showed that reduced dose VP CT with low tube-current time product might yield sufficient image quality for the diagnosis of acute stroke (13)(14)(15)(16). However, perfusion impairment in patients with cerebral vasospasm is often more subtle, detectability might be compromised at lower dose levels (17).…”
Section: Data Acquisitionmentioning
confidence: 99%